(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Query with Facet Mining mechanism helps user to search, locate and access appropriate data from online web contents. The system generates facets not only for given query but also for whole collection. In the paper, proposed system discovers to mechanically find query related feature of search for open-domain queries using search engine. Facets for a query are automatically pull out from top search list for web. It enables user to recognize query aspects which promote improved search experience of user. In this paper, proposed system retains facets output of the query in database that can be delivered to the user searching for same query .and this improves the performance of the system and user search experience. When a user relates with the system with query, the system creates Facets for his query and give back to the user. Also it stored the generated facets in a database table. When any random user request same query, the system will first check facets for query in database, and it returned if it is available otherwise it generates facets for new query. So it saves system processing time for duplicate query and improves the performance. System will display pre-query for user entered query according to past searched history.